Forest Certification, its Scheme and Process - Acharya, Bishnu (The Initiation, 2011)
Forest Certification (FC) is a process of certifying any forest by an independent party. During the 80’s when forest was heavily destructed, the need of the forest certification was felt, and was accepted worldwide. he interest for FC varies as per the needs of the people and/or organizations involved. Various organizations are involved in the certification process, major ones being Forest Stewardship Council (FSC), Program for the Endorsement of the Forest Certification (PEFC) and other process vary from country to country. This article deals with the certification bodies, process involved and the responsibilities of the stakeholders. DOI: http://dx.doi.org/10.3126/init.v4i0.5546 The Initiation Vol.4 2011 125-132